Analysis of Window Width and Window Level Variation on Anatomical Information of Abdominal CT scan in Cases of Intra-Abdominal Mass Using Siemens 16 Slice Device - Faisal Muhammad; Nurbaiti Nurbaiti; Wahyu Hidayat; Eka Putra Syarif Hidayat; Sriyatun Sriyatun (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Optimal adjustment of window width (WW) and window level (WL) is essential for improving anatomical visualization on abdominal CT scans in patients with intra-abdominal masses. Objective: To analyze the effects of different WW and WL settings on abdominal CT images and determine the optimal values for evaluating intra-abdominal mass cases. Methods: This quantitative observational study analyzed abdominal CT scans from six patients with radiologist-confirmed intra-abdominal masses. Images were reconstructed using different WW and WL combinations, and three experienced observers independently assessed the resulting anatomical information to identify the most appropriate image settings. Results: Significant differences were observed in the anatomical information produced by the various WW and WL settings. The combination of WW 300 HU and WL 60 HU provided superior visualization of abdominal anatomical structures and lesion characteristics compared with the other settings evaluated. These parameters consistently yielded clearer image contrast and improved diagnostic interpretation across the observers. Conclusion: Variations in WW and WL significantly influence the diagnostic quality of abdominal CT images in patients with intra-abdominal masses. A setting of WW 300 HU and WL 60 HU is recommended as the optimal protocol for enhancing anatomical visualization and supporting accurate radiological assessment in routine clinical practice.